Patterns of B Cell Repletion Following Rituximab Therapy in a Pediatric Rheumatology Cohort - Mitchell, Chace (ACR Open Rheumatol, 2019)
OBJECTIVE: To investigate the association between demographic characteristics, disease characteristics, the number of rituximab (RTX) rounds, and concurrent immunosuppression on B cell level repletion following RTX therapy. METHODS: A retrospective chart review of 112 children who met inclusion criteria and were treated with RTX at a single institution was performed. Demographic, clinical, and laboratory data were extracted and compared. CD19 levels were reviewed at 6 and 12 months post‐RTX with depletion defined as fewer than 10 cells/μL and complete repopulation to normal levels defined as 170 cells/μL or more. RESULTS: Among patients with CD19 levels, 48% of patients remained depleted at 6 months, 89% were repleted with 10 cells/μL or more by 12 months, and 46% remained below normal levels at 12 months following infusion. There was no significant association between the number of RTX rounds or underlying disease and persistent depletion below normal levels at 12 months following RTX infusion. Depletion at 6 months was associated with a 79% chance of persistent depletion below normal levels at 12 months. The association between concurrent cyclophosphamide (CYC) and repletion of 10 cells/μL or more at 6 (P = 0.091) and 12 months (P = 0.087) trended toward significance with no significant association between CYC and persistent depletion below normal levels. CONCLUSION: RTX therapy for pediatric rheumatic diseases is well‐tolerated and results in variable repletion and normalization of B cell numbers at 6 and 12 months. B cell repletion in children is variable and independent of underlying disease and of the number of RTX infusions.